Blast loading of bumper shielded hybrid two-core Miura-ori/honeycomb core sandwich plates. (August 2018) - Pydah, Anup; Batra, R.C.
Abstract: We analyze transient elasto-plastic deformations of two-core sandwich plates with and without a bumper and subjected to blast loads with the objective of ascertaining the energy dissipated due to plastic deformations. The facesheets and the core are assumed to be made of a high strength steel modeled as an isotropic material that obeys the von Mises yield criterion with linear strain hardening. It is first shown that considering a material failure criterion and deleting failed elements does not noticeably affect the energy dissipated in a sandwich plate. Subsequent analyses of two-core structures with and without a blast shield ignore the material failure and assume facesheets to be perfectly bonded to the core. The nonlinear transient problems have been numerically analyzed with the commercial finite element software, ABAQUS/ Explicit. Four different two-core sandwich plates obtained by varying locations of the Miura-ori and honeycomb cores are considered. Results without a shield indicate that using a Miura-ori core beneath the topmost facesheet dissipates more energy for moderate blast loads, while a combination of a honeycomb and a Miura-ori core has the least facesheet deflections. The effects of using a blast shield or a bumper, at a fixed standoff distance from a honeycomb-Miura sandwich panel, is studied by ensuring that the shield and the sandwich structure combination has the same areal density as the sandwich panel without the shield. It is found that for a given blast load, using the shield significantly reduces the energy dissipated in the sandwich panel, the bottom facesheet maximum centroidal deflection and the maximum plastic strain in the cores when compared with equal-weight panels without a shield. For the same energy dissipation, the structure with a blast shield has approximately 42% less weight than that without the shield. Abstract : Highlights: Using Miura-ori core in hybrid two-layered sandwich panel considerably enhances energy dissipation. Increases the number of unit cells from 3, 3 to 7, 7 for the Miura-Miura panel more than doubles the energy dissipated. Honeycomb-Miura hybrid sandwich panels reduce facesheet deflections and reaction forces at clamped edges. For the same areal density, a blast shield above the hybrid sandwich panel is highly effective in mitigating the panel deformations.